Quantifying explosive actions in international women`s soccer - Meylan, C.; Trewin, J.; McKean, K. (International Journal of Sports Physiology and Performance, 2017)
The aims of the current study were to examine the external validity of inertial-based parameters (inertial movement analysis [IMA]) to detect multiplanar explosive actions during maximal sprinting and change of direction (COD) and to further determine its reliability, set appropriate magnitude bands for match analysis, and assess its variability during international women`s soccer matches. Twenty U20 female soccer players, wearing global positioning system (GPS) units with a built-in accelerometer, completed 3 trials of a 40-m sprint and a 20-m sprint with a change of direction to the right or left at 10 m. Furthermore, 13 women`s national-team players (157 files; 4-27 matches/player) were analyzed to ascertain match-to-match variability. Video synchronization indicated that the IMA signal was instantaneous with explosive movement (acceleration, deceleration, COD). Peak GPS velocity during the 40-m sprint showed similar reliability (coefficient of variation [CV] = 2.1%) to timing gates but increased before and after COD (CV = 4.5-13%). IMA variability was greater at the start of sprints (CV = 16-21%) than before and after COD (CV = 13-16%). IMA threshold for match analysis was set at 2.5 m/s.s by subtracting 1 SD from the mean IMA during sprint trials. IMA match variability (CV = 14%) differed from high-speed GPS metrics (35-60%). Practitioners are advised that timing lights should remain the gold standard for monitoring sprint and acceleration capabilities of athletes. However, IMA could be a reliable method to monitor explosive actions between matches and assess changes due to various factors such as congested schedule, tactics, heat, or altitude.